Exploring why and how commercial organizations contribute to OpenStreetMap - Héctor Ochoa-Ortiz; Barbara Re (Annals of GIS)
OpenStreetMap (OSM) is a Digital Commons platform, collaboratively developed, and centred on creating an accurate spatial representation of the world. Its flexibility and open nature have attracted multiple commercial organizations to use data from and contribute to the platform in several ways. This study examines the motivations and methods of commercial organizations to contribute to OSM, based on semi-structured interviews with employees of 25 commercial organizations and the Overture Maps Foundation. Five distinct ways of contribution have been found: data editing, tool development and/or funding, event sponsoring, OSM Foundation or related funding, and community building. The motivations behind their contribution to the project are a mixture of their own business benefits, such as to improve the data quality in a source the companies use, and social value motivations, like community-building. Commercial organizations have also encountered barriers with OSM in its use and contribution, ultimately resulting in the recent development of the Overture Maps platform. OSM should, in turn, provide a space where those self-motivations can be turned into social good and, at the same time, achieve an inviting space for all stakeholders (including commercial organizations) to ensure project sustainability, without falling into the tragedy of the commons.